Welded joint

By containing Si and Al in the steel plate and decarbonizing the periphery of the welded part after high dew point annealing, the ferrite phase is stabilized, and the problem of LME cracks in the welded joint is solved and the endurance of the welded joint is improved.

CN119816613APending Publication Date: 2025-04-11NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063333.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-09-06
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When manufacturing welded joints, it is difficult to effectively suppress liquid metal embrittlement (LME) cracks, especially when using high-strength steel plates.

Method used

By containing Si and Al in a large amount of steel plate, an appropriate surface state is made, and after annealing at high dew point, the ferrite phase is stabilized to suppress LME cracks.

Benefits of technology

The LME crack suppression during the manufacturing of welded joints is achieved, the endurance of the welded joints is improved, and the welding quality is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816613A_ABST
    Figure CN119816613A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a welded joint in which LME cracks during production are suppressed. This welded joint is characterized in that a plated steel sheet constituting the welded joint has a prescribed chemical composition, and in a non-heat-affected part of the welded joint, the depth at which the C concentration measured by GDS is 0.05% or less in the depth direction of the base steel sheet starting from the interface between the plated layer of the plated steel sheet and the base steel sheet is 10 [mu] m or more, and the thickness of the welded joint is 10 [mu] m or more. The roughness (Ra) of the interface between the plating layer of the plated steel sheet and the base material steel sheet in the non-heat-affected portion is 3.0 [mu] m or less, and the roughness (Ra) of the plating layer of the plated steel sheet in the depth direction of the base material steel sheet starting from the interface between the plating layer of the plated steel sheet and the base material steel sheet at a position 500 [mu] m from the end of the crimped portion of the welded joint. The thickness of the layer having a ferrite phase area ratio of 90% or more is 15 [mu] m or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a welded joint, and more particularly to a welded joint in which LME cracks are suppressed during manufacturing. Background Art

[0002] In recent years, the strength of steel sheets used in various fields such as automobiles, home appliances, and building materials has been increasing. For example, in the automotive field, the use of welded joints obtained by spot welding high-strength steel sheets is increasing in order to improve fuel efficiency and reduce the weight of the vehicle body.

[0003] In welding of zinc-plated steel sheets, especially high-strength steel sheets, a reduction in weldability due to liquid metal embrittlement (LME) cracking may become a problem, as described in Patent Document 1, for example. LME cracking is believed to occur when the surface layer of the steel sheet transforms into austenite during welding, the molten zinc that intrudes into the grain boundaries embrittles the steel sheet, and further tensile stress is applied to the steel sheet during welding.

[0004] In addition, as disclosed in Non-Patent Document 1, regarding LME cracking, it is known that the LME sensitivity of the grain boundary of the ferrite phase is lower than that of the austenite grain boundary.

[0005] It should be noted that Patent Document 2 discloses a steel plate having 3000 to 6000 cracks / mm2 on the surface layer of the steel plate as a steel plate having improved weldability by suppressing LME cracks. 2 A steel plate in which Si oxide particles having a particle size of 20 nm or more are present in an appropriate particle size distribution with a number density of 1.547 W.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2019 / 116531

[0009] Patent Document 2: International Publication No. 2020 / 218575

[0010] Non-patent literature

[0011] Non-patent document 1: Influence of the starting microstructure of an advancedhigh strength steel on the characteristics of Zn-Assisted liquid metalembrittlement, D.Bhattacharya et.al., Materials Science and Engineering: A, Vol.804, 2021 Summary of the invention

[0012] Technical problem to be solved by the invention

[0013] In order to prevent LME cracks when manufacturing welded joints, it is effective to suppress the intrusion of Zn and the like contained in the plating layer into the steel sheet after austenite transformation. In this regard, there is room for improvement.

[0014] The present invention has been made in view of such actual conditions, and a technical object of the present invention is to provide a welded joint in which LME cracks are suppressed during manufacturing.

[0015] Means for solving technical problems

[0016] The present inventors have conducted intensive research on means for solving the above-mentioned technical problems. As a result, they have found that by adding a large amount of Si and Al to a steel plate to be spot welded, making the steel plate in an appropriate surface state and performing high dew point annealing, the weld periphery is decarburized, and the ferrite (α) phase is stabilized, and the surface layer of the steel plate is covered with a ferrite phase with a low solid solution amount of C. It is possible to suppress LME by maintaining the ferrite phase in a stable state even when manufacturing a welded joint.

[0017] The present invention has been completed as a result of further studies based on the above findings, and the gist of the present invention is as follows.

[0018] (1) A weld joint, characterized in that it comprises a plurality of overlapping steel plates, a nugget for joining the plurality of steel plates, a spot weld portion having a crimping portion and a heat-affected portion formed around the nugget, and a separation portion formed around the crimping portion, wherein at least one of the plurality of steel plates is a plated steel plate having a base steel plate and a plating layer, the plating layer is formed on at least a surface corresponding to the overlapping surface of the plurality of steel plates and contains Zn, the tensile strength of the plated steel plate is 780 MPa or more, and the base steel plate is The chemical composition of the steel plate is as follows by mass %: C: 0.05-0.40%, Si: 0.7-3.0%, Mn: 0.1-5.0%, sol.Al: 0.7-2.0%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B: 0-0.010%, Ti: 0-0.150%, Nb: 0-0.150%, V: 0-0.150%, Cr: 0-2.00%, Ni: 0-2.0 0%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0-1.00%, Ca: 0-0.100%, Mg: 0-0.100%, Zr: 0-0.100%, Hf: 0-0.100%, REM: 0-0.100%, the balance being Fe and impurities, the total content of Si and sol.Al being 1.8% or more, in the non-heat-affected portion of the welded joint, at the interface between the above-mentioned coating layer of the above-mentioned coating steel sheet and the above-mentioned base steel sheet as a starting point In the depth direction of the above-mentioned base steel plate, the depth at which the C concentration measured by GDS is less than 0.05% is more than 10μm, the roughness of the interface between the above-mentioned coating of the above-mentioned plated steel plate and the above-mentioned base steel plate is less than 3.0μm in terms of Ra, and at a position 500μm outward from the end of the above-mentioned crimping portion, in the depth direction of the above-mentioned base steel plate starting from the interface between the above-mentioned coating of the plated steel plate and the above-mentioned base steel plate, the thickness of the layer having an area ratio of ferrite phase of more than 90% is more than 15μm.

[0019] (2) A weld joint according to (1) above, characterized in that, in the non-heat-affected portion of the weld joint, the depth at which the C concentration measured by GDS is less than 0.05% in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate is 15 μm or more.

[0020] (3) A welded joint according to (1) above, characterized in that, at a position 500 μm outward from the end of the crimped portion, in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate, the thickness of the layer having an area ratio of ferrite phase of 90% or more is 30 μm or more.

[0021] (4) A welded joint according to (1) above, characterized in that, in the non-heat-affected portion of the welded joint, in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate, the depth at which the C concentration measured by GDS is less than 0.05% is 15 μm or more, and at a position 500 μm outward from the end of the crimped portion, in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate, the thickness of a layer having an area ratio of 90% or more is 30 μm or more.

[0022] (5) The weld joint according to any one of (1) to (4) above, wherein the roughness of the interface between the plating layer of the plated steel sheet and the base steel sheet in the non-heat-affected portion is 2.0 μm or less in terms of Ra.

[0023] Effects of the Invention

[0024] According to the present invention, it is possible to obtain a welded joint in which LME cracks are suppressed during production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a diagram schematically showing an example of a welded joint according to the present invention.

[0026] Figure 2 This is a diagram showing a layered ferrite (α) phase formed around the weld portion of the weld joint of the present invention.

[0027] Figure 3 It is a figure explaining the evaluation of LME resistance in Examples. DETAILED DESCRIPTION

[0028] The present invention will be described below. The present invention is not limited to the following embodiments. First, the outline of improving the LME resistance during manufacturing in the welded joint of the present invention will be described.

[0029] LME cracks are caused by the surface of the steel plate being heated during spot welding, and the steel plate structure of the surface layer is transformed into austenite, and the molten plating enters the steel plate structure along the grain boundaries of the austenite, thereby embrittlement of the grain boundaries. It is believed that tensile stress is applied to the steel plate during welding, so LME cracks are generated. The welded joint of the present invention improves the LME resistance of the welded joint during manufacturing by forming a structure on the surface of the steel plate. It should be noted that in this specification, the surface layer of the steel plate refers to the range from the outermost surface of the steel plate to a depth of 100μm.

[0030] When the C element is contained in the surface layer of the steel plate, LME cracks are likely to occur. Therefore, suppressing the C concentration in the surface layer of the steel plate to a low level is effective in preventing LME cracks. Generally, when the steel plate is heated as in annealing, external oxidation occurs and oxides (scale) are formed on the surface of the steel plate, so decarburization is difficult. Therefore, it is difficult to reduce the C concentration in the surface layer of the steel plate. On the other hand, in the welded joint of the present invention, in the non-heat-affected portion, starting from the interface between the coating of the plated steel plate constituting the welded joint and the base steel plate, the depth at which the C concentration measured by GDS is less than 0.05% is greater than 10 μm in the depth direction of the base material. This means that in the surface layer of the plated steel plate constituting the welded joint, the concentration of C, an element that is likely to cause LME, is low, and this state is maintained even after the welded joint is manufactured.

[0031] In the present invention, when manufacturing the plated steel sheet constituting the welded joint, the surface roughness of the base steel sheet is not increased to impart a strong strain to the surface layer, and the steel sheet is annealed at a high dew point. As a result, oxygen diffuses into the steel sheet to form internal oxides, and the formation of external oxides can be suppressed. As a result, the C concentration of the surface layer of the base steel sheet is reduced.

[0032] Furthermore, in the welded joint of the present invention, at a position 500 μm outward from the end of the crimped portion, starting from the interface between the coating of the plated steel plate and the base steel plate, in the depth direction of the base material, the thickness of the layer whose area ratio of the ferrite phase is 90% or more is 15 μm or more. That is, the ferrite phase also exists stably around the heat-affected portion. Here, the "heat-affected portion" refers to the portion of the steel plate that has not been melted due to changes in the structure, metallurgical properties, mechanical properties, etc. caused by welding heat. The heat-affected portion can be confirmed by observing the cross section in the thickness direction of the plate using SEM. In addition, the "non-heat-affected portion" is the portion other than the heat-affected portion. Furthermore, it is believed that the ferrite can be stabilized by the effect of the composite addition of Si and sol.Al in the steel plate.

[0033] That is, the welded joint of the present invention has a combined effect of high Si and sol.Al contents in the plated steel sheet constituting the welded joint, imparting strain to the surface layer before annealing, and controlling the dew point during annealing. Even if the surface layer of the plated steel sheet is affected by the heat caused by welding, the C concentration is low, and a layer with a high area ratio of ferrite is formed, thereby improving the LME resistance during the manufacture of the welded joint.

[0034] Hereinafter, the present invention will be described in detail.

[0035] 《Welding joints》

[0036] First, refer to Figure 1 The welded joint of the present invention is described. Figure 1 As shown in (a), the welded joint of the present invention is formed by using a welding electrode A to weld multiple ( Figure 1 The steel sheet 1 is manufactured by spot welding (two in the figure). An overlapping surface 6 is formed on the surface where the plurality of steel sheets 1 are in contact.

[0037] Figure 1 (b) shows a welded joint in which two steel plates are welded by spot welding. The welded joint of the present invention comprises a plurality of overlapping steel plates 1 and a nugget 2 for joining the plurality of steel plates. The nugget 2 is a portion where the steel component and the plating component are melted and solidified by spot welding. A crimping portion 3 where two steel plates 1 are crimped is formed around the nugget 2. A separation portion 4 exists around the crimping portion 3. The separation portion 4 is a portion where welding or crimping based on spot welding does not occur, and is a portion where the two steel plates 1 are not in direct contact. The "end of the crimping portion" refers to the position closest to the separation portion 4 in the crimping portion 3. From the end of the crimping portion to the "outside" refers to the direction from the end of the crimping portion 3 toward the open portion of the separation portion 4. In addition, around the nugget 2, a heat-affected zone 5 is formed where the structure, metallurgical properties, mechanical properties, etc. are changed due to the welding heat.

[0038] The plurality of steel plates constituting the welded joint of the present invention may include both a plated steel plate having a base steel plate and a plated layer and a non-plated steel plate that is not plated, but at least one of the plurality of steel plates is a plated steel plate. The plated layer is formed at least on a surface corresponding to the overlapping surface 6 of the steel plate. In addition, the tensile strength of the plated steel plate is 780 MPa or more.

[0039] As described above, LME cracks are generated when molten zinc plating exists on the surface of a high-strength (tensile strength of 780 MPa or more) steel plate during welding. Therefore, when considering, for example, a welded joint composed of two steel plates, if one of the two steel plates is a high-strength plated steel plate, LME cracks may occur. The welded joint of the present invention is an invention that includes a high-strength plated steel plate in the steel plates constituting the welded joint and can suppress LME cracks during the manufacture of the welded joint.

[0040] <Chemical composition of steel sheet>

[0041] Next, the chemical composition of the base steel plate of the plated steel plate constituting the welded joint is described. Hereinafter, "%" in the chemical composition means "mass %". In addition, in the numerical range of the chemical composition, the numerical range expressed by "to" means a range including the numerical values ​​recorded before and after "to" as the lower limit and upper limit.

[0042] (C: 0.05~0.40%)

[0043] C (carbon) is an element that ensures the strength of steel. In order to obtain a tensile strength of 780 MPa or more, which is the object of the present invention, the C content is set to 0.05-0.40% in consideration of the balance with weldability, and in order to prevent the C concentration in the surface layer of the base steel plate from becoming too high. When the C content is too high, the C concentration in the surface layer of the base steel plate will not decrease even through the high dew point annealing described later. The C content may be 0.07% or more, 0.10% or more, or 0.12% or more. The C content may be 0.35% or less, 0.30% or less, or 0.25% or less.

[0044] (Si: 0.7~3.0%, sol.Al: 0.7~2.0%, Si+sol.Al≥1.8%)

[0045] Si (silicon) is an element that promotes ferrite stabilization and decarburization by being added in combination with Al (aluminum). In order to obtain the effect of LME inhibition, Si: 0.7-3.0%, sol.Al: 0.7-2.0%, and the total content of Si and sol.Al is set to 1.8% or more. Sol.Al refers to acid-soluble Al that is soluble in acid without becoming oxides such as Al2O3, and is determined as Al measured by deducting the insoluble residue on the filter paper produced during the analysis of Al. The content of Si can be 0.8% or more, 0.9% or more, or 1.0% or more. The content of Si can be 2.8% or less, 2.5% or less, or 2.0% or less. The content of sol.Al can be 0.8% or more, 0.9% or more, or 1.0% or more. The content of sol.Al can be 1.8% or less, 1.6% or less, or 1.5% or less. The total value of the contents of Si and sol.Al may be 1.9% or more, 2.0% or more, or 2.2% or more.

[0046] (Mn: 0.1~5.0%)

[0047] Mn (manganese) is an element effective in improving the strength of the steel plate by obtaining a hard structure. Considering the balance between the strength of the steel and the reduction in workability due to Mn segregation, the Mn content is set to 0.1-5.0%. The Mn content may be 0.5% or more, 1.0% or more, or 1.5% or more. The Mn content may be 4.5% or less, 4.0% or less, or 3.5% or less.

[0048] (P: 0.0300% or less)

[0049] P (phosphorus) is an impurity generally contained in steel. When the content of P exceeds 0.0300%, there is a risk of reduced weldability. Therefore, the content of P is set to 0.0300% or less. The content of P may be 0.0200% or less, 0.0100% or less, or 0.0050% or less. It is preferred that P is not contained, and the lower limit of the content of P is 0%. From the viewpoint of dephosphorization cost, the content of P may exceed 0%, 0.0001% or more, or 0.0005% or more.

[0050] (S: 0.0300% or less)

[0051] S (sulfur) is an impurity usually contained in steel. When the S content exceeds 0.0300%, there is a risk that weldability decreases, and the amount of MnS precipitation increases, thereby reducing workability such as bendability. Therefore, the S content is set to 0.0300% or less. The S content can be less than 0.0100%, less than 0.0050%, less than 0.0030%, less than 0.0020% or less than 0.0010%. It is preferred that S is not contained, and the lower limit of the S content is 0%. From the perspective of desulfurization cost, the S content can exceed 0%, be more than 0.0001% or be more than 0.0005%.

[0052] (N: 0.0100% or less)

[0053] N (nitrogen) is an impurity generally contained in steel. When the N content exceeds 0.0100%, there is a risk of reduced weldability. Therefore, the N content is set to 0.0100% or less. The N content may be 0.0080% or less, 0.0050% or less, 0.0030% or less, 0.0020% or less, or 0.0010% or less. Preferably, N is not contained, and the lower limit of the N content is 0%. From the viewpoint of manufacturing cost, the N content may exceed 0%, 0.0001% or more, 0.0002% or more, 0.0003% or more, or 0.0005% or more.

[0054] (B: 0~0.010%)

[0055] B (boron) is an element that improves hardenability and contributes to the improvement of strength, and segregates at grain boundaries to strengthen grain boundaries and thus improve toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the content of B is 0%. This effect can be obtained even if it contains a trace amount, but the content of B when contained is preferably 0.0001% or more. The content of B can be more than 0.0002%, more than 0.0003%, more than 0.0005%, more than 0.0007% or more than 0.0010%. On the other hand, from the viewpoint of ensuring sufficient toughness, the content of B is set to less than 0.010%. The content of B can be less than 0.0080%, less than 0.0060%, less than 0.0050%, less than 0.0040% or less than 0.0030%.

[0056] (Ti: 0~0.150%)

[0057] Ti (titanium) is an element that precipitates in the form of TiC during the cooling of steel and contributes to the improvement of strength, so it can be contained as needed. Since it is not an essential element, the lower limit of the Ti content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Ti content when contained is preferably 0.0001% or more. The Ti content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, 0.0007% or more, or 0.0010% or more. On the other hand, when it is contained excessively, there is a risk of coarse TiN being generated and toughness being impaired, so the Ti content is set to 0.150% or less. The Ti content can be 0.1000% or less, 0.0500% or less, 0.0300% or less, 0.0200% or less, 0.0100% or less, 0.0050% or less, or 0.0030% or less.

[0058] (Nb: 0~0.150%)

[0059] Nb (niobium) is an element that contributes to the improvement of strength by improving hardenability, so it can be contained as needed. Since it is not an essential element, the lower limit of the Nb content is 0%. This effect can be obtained even if a trace amount is contained, but the Nb content when contained is preferably 0.001% or more. The Nb content can be 0.002% or more, 0.003% or more, 0.005% or more, or 0.008% or more. On the other hand, from the viewpoint of ensuring sufficient toughness, the Nb content is set to 0.150% or less. The Nb content can be 0.100% or less, 0.060% or less, 0.050% or less, 0.040% or less, or 0.030% or less.

[0060] (V: 0~0.150%)

[0061] V (vanadium) is an element that contributes to the improvement of strength by improving hardenability, so it can be contained as needed. Since it is not an essential element, the lower limit of the V content is 0%. This effect can be obtained even if it contains a trace amount, but the V content when contained is preferably 0.001% or more. The V content can be more than 0.002%, more than 0.003% or more than 0.005%. On the other hand, from the viewpoint of ensuring sufficient toughness, the V content is set to less than 0.150%. The V content can be less than 0.100%, less than 0.060%, less than 0.050%, less than 0.040%, less than 0.030% or less than 0.020%.

[0062] (Cr: 0~2.00%)

[0063] Cr (chromium) is effective for improving the hardenability of steel and the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Cr content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Cr content when contained is preferably set to 0.001% or more. The Cr content can be more than 0.01%, more than 0.02%, more than 0.03%, more than 0.05% or more than 0.08%. On the other hand, when it is contained excessively, there is a risk of a large amount of Cr carbides being formed, and the hardenability is impaired, so the Cr content is set to less than 2.00%. The Cr content can be less than 1.80%, less than 1.50%, less than 1.20%, less than 1.00%, less than 0.70%, less than 0.50% or less than 0.30%.

[0064] (Ni: 0~2.00%)

[0065] Ni (nickel) is effective for improving the hardenability of steel and improving the strength of steel, so it can also be contained as required. Since it is not an essential element, the lower limit of the content of Ni is 0%. This effect can be obtained even if it contains a trace amount, but the content of Ni when contained is preferably more than 0.001%. The content of Ni can be more than 0.01% or more than 0.02%. On the other hand, excessive addition of Ni can cause cost increase, so the content of Ni is set to less than 2.00%. The content of Ni can be less than 1.80%, less than 1.50%, less than 1.20%, less than 1.00%, less than 0.80%, less than 0.50%, less than 0.30%, less than 0.20%, less than 0.10% or less than 0.05%.

[0066] (Cu: 0-2.00%)

[0067] Cu (copper) is effective for improving the hardenability of steel and the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the content of Cu is 0%. This effect can be obtained even if it contains a trace amount, but the content of Cu when contained is preferably more than 0.0001%. The content of Cu can be more than 0.0002%, more than 0.0003% or more than 0.0005%. On the other hand, from the viewpoint of suppressing the reduction of toughness and the cracks of the slab after casting, the content of Cu is set to less than 2.00%. The content of Cu can be less than 1.8000%, less than 1.5000%, less than 1.2000%, less than 1.0000%, less than 0.5000%, less than 0.1000%, less than 0.0500%, less than 0.0100%, less than 0.0050%, less than 0.0030%, or less than 0.0020%.

[0068] (Mo: 0~1.00%)

[0069] Mo (molybdenum) is effective for improving the hardenability of steel and the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the Mo content is 0%. This effect can be obtained even if it contains a trace amount, but the Mo content when contained is preferably 0.001% or more. The Mo content can be more than 0.01%, more than 0.02%, more than 0.03%, more than 0.05% or more than 0.08%. On the other hand, from the viewpoint of suppressing the reduction of toughness, the Mo content is set to less than 1.00%. The Mo content can be less than 0.90%, less than 0.70%, less than 0.50% or less than 0.30%.

[0070] (W: 0~1.00%)

[0071] W (tungsten) is effective for improving the hardenability of steel and the strength of steel, so it can also be contained as needed. Since it is not an essential element, the lower limit of the content of W is 0%. This effect can be obtained even if it contains a trace amount, but the content of W when contained is preferably 0.001% or more. The content of W can be more than 0.002%, more than 0.005% or more than 0.01%. On the other hand, from the viewpoint of suppressing the reduction of toughness, the content of W is set to less than 1.00%. The content of W can be less than 0.90%, less than 0.70%, less than 0.50%, less than 0.30%, less than 0.10%, less than 0.05% or less than 0.03%.

[0072] (Ca: 0~0.100%)

[0073] Ca (calcium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Ca content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Ca content when contained is preferably 0.0001% or more. The Ca content can be 0.0002% or more. On the other hand, when it is contained excessively, the deterioration of the surface properties is sometimes obvious, so the Ca content is set to 0.100% or less. The Ca content can be less than 0.0800%, less than 0.0500%, less than 0.0100%, less than 0.0050%, less than 0.0030%, less than 0.0020%, less than 0.0010%, less than 0.0008% or less than 0.0005%.

[0074] (Mg: 0~0.100%)

[0075] Mg (magnesium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Mg content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Mg content when contained is preferably 0.0001% or more. The Mg content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, or 0.0008% or more. On the other hand, when it is contained excessively, the deterioration of the surface properties is sometimes obvious, so the Mg content is set to 0.100% or less. The Mg content can be 0.090% or less, 0.080% or less, 0.050% or less, 0.010% or less, 0.005% or less, or 0.003% or less.

[0076] (Zr: 0~0.100%)

[0077] Zr (zirconium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Zr content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Zr content when contained is preferably 0.001% or more. The Zr content can be more than 0.002%, more than 0.003%, more than 0.005% or more than 0.010%. On the other hand, when it is contained excessively, the deterioration of the surface properties is sometimes obvious, so the Zr content is set to less than 0.100%. The Zr content can be less than 0.080%, less than 0.050%, less than 0.040% or less than 0.030%.

[0078] (Hf: 0~0.100%)

[0079] Hf (Hafnium) is an element that helps control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the Hf content is 0%. This effect can be obtained even if it is contained in a trace amount, but the Hf content when contained is preferably 0.0001% or more. The Hf content can be 0.0002% or more, 0.0003% or more, 0.0005% or more, or 0.0008% or more. On the other hand, when it is contained excessively, the deterioration of the surface properties is sometimes obvious, so the Hf content is set to 0.100% or less. The Hf content can be 0.050% or less, 0.030% or less, 0.010% or less, 0.005% or less, or 0.003% or less.

[0080] (REM: 0~0.100%)

[0081] REM (rare earth element) is an element that helps to control inclusions, especially fine dispersion of inclusions, and has the effect of improving toughness, so it can be contained as needed. Since it is not an essential element, the lower limit of the REM content is 0%. This effect can be obtained even if it is contained in a trace amount, but the REM content when contained is preferably 0.0001% or more. The REM content can be 0.0003% or more or 0.0005% or more. On the other hand, when it is contained excessively, the deterioration of the surface properties sometimes becomes obvious, so the REM content is set to 0.100% or less. The REM content can be 0.0500% or less, 0.0300% or less, 0.0100% or less, 0.0050% or less, 0.0030% or less, or 0.0020% or less. In addition, REM is the abbreviation of RareEarth Metal, which refers to an element belonging to the lanthanide series. REM is usually added in the form of mixed rare earth.

[0082] In the base steel plate of the plated steel plate constituting the welded joint of the present invention, the remainder other than the above chemical components is composed of Fe and impurities. Here, impurities refer to components that are mixed into the raw materials such as ores and scraps when the steel plate is industrially manufactured due to various reasons in the manufacturing process, and do not adversely affect the LME resistance of the welded joint of the present invention when it is manufactured.

[0083] The chemical composition of the base steel plate can be analyzed by an elemental analysis method known to those skilled in the art, for example, by inductively coupled plasma mass spectrometry (ICP-MS). Among them, C and S can be measured by combustion-infrared absorption method, and N can be measured by inert gas melting-thermal conductivity method. These analyses can be performed using samples taken from the base steel plate according to the method of JIS G0417: 1999.

[0084] One or more of the multiple steel plates constituting the weld joint of the present invention is a plated steel plate having a base steel plate and a plating layer. The plating layer contains Zn. In addition, the plating layer is formed at least on the surface corresponding to the overlapping surface of the multiple steel plates. There is no particular restriction if the plating layer contains Zn. As an example, Zn-0.2%Al, Zn-0.5%Al, Zn-1.5%Al-1.5%Mg, Zn-20%Al-7%Mg, and Zn-30%Al-10%Mg can be cited. The plating layer can also be formed on a surface other than the surface corresponding to the overlapping surface of the multiple steel plates.

[0085] The chemical composition of the plating layer can be determined by dissolving the plating layer in an acid solution to which an inhibitor for inhibiting corrosion of a base steel plate is added, and measuring the resulting solution by ICP (high frequency inductively coupled plasma) emission spectroscopy.

[0086] The thickness of the plating layer can be, for example, 3 to 50 μm. In addition, the amount of the plating layer applied is not particularly limited, but can be, for example, 10 to 170 g / m per side. 2 In the present invention, the coating adhesion amount is determined by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the base steel plate is added, and by the weight change of the coating before and after pickling and stripping. The coating thickness may be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or more. The coating thickness may be 40 μm or less, or 30 μm or less. The coating adhesion amount may be 20 g / m per single side. 2 Above, 30g / m 2 Above, 40g / m 2 Above or 50g / m 2 The coating weight can be 150g / m per side. 2 Below, 130g / m 2 Below, 120g / m 2 Below or 100g / m 2 the following.

[0087] The plate thickness of the plated steel plate constituting the welded joint of the present invention is not particularly limited. For example, it can be set to 0.6 to 3.2 mm. The plate thickness can be 0.8 mm or more or 1.0 mm or more. The plate thickness can be 3.0 mm or less, 2.6 mm or less, 2.4 mm or less, 2.2 mm or less, 2.0 mm or less, or 1.8 mm or less.

[0088] Next, the structure of the plated steel sheet constituting the welded joint will be described.

[0089] [C concentration in non-heat-affected zone]

[0090] In the welded joint of the present invention, in the non-heat affected portion, in the depth direction of the base steel plate starting from the interface between the coating of the plated steel plate and the base steel plate, the depth at which the C concentration measured by GDS is less than 0.05% is more than 10 μm. The portion of the heat affected portion where the material properties change due to heat during the spot welding process can be confirmed by SEM observation. The non-heat affected portion is the portion other than the heat affected portion. If it is at a position more than 5 mm from the outer end of the spot weld, it can be regarded as a non-heat affected portion, so the measurement is performed at a position more than 5 mm from the outer end of the spot weld.

[0091] Since the sensitivity of LME decreases when the C concentration decreases, the LME suppression effect during the manufacture of the welded joint is improved by reducing the C concentration in the non-heat-affected zone. In addition, C is an austenite stabilizing element, so by making it a small amount, the ferrite phase with low LME sensitivity described later is stabilized.

[0092] As described above, such a structure can be obtained by setting the chemical composition of the base steel sheet of the plated steel sheet to a component containing a large amount of Si and Al, performing the heat treatment described later, and performing spot welding.

[0093] If the depth at which the C concentration is 0.05% or less is 10 μm or more, the LME suppression effect during manufacturing can be obtained, so the upper limit of the depth is not particularly limited, and the depth may be, for example, 50 μm or less, 40 μm or less, or 30 μm or less. The depth at which the C concentration is 0.05% or less is preferably 25 μm or more.

[0094] GDS measurement was performed 5 times in the plate thickness direction, and the average value was taken as the C concentration. The measurement conditions are as follows. The starting point of "depth" is the interface between the base steel plate and the coating. The interface between the base steel plate and the coating is set to the position where the Fe concentration measured in the GDS measurement is 93% at a depth of 150 μm.

[0095] Equipment: High-frequency glow discharge luminescence analysis device (manufactured by LECO Japan Co., Ltd., model "GDS850A")

[0096] Ar gas pressure: 0.3MPa

[0097] Cathode diameter: 4mmφ

[0098] RF power: 30W

[0099] Measuring time: 200 to 1500 seconds

[0100] [Interface roughness of non-heat-affected zone]

[0101] The roughness of the interface between the coating and the base steel plate of the plated steel plate in the non-heat-affected zone of the welded joint of the present invention is 3.0 μm or less in terms of the arithmetic mean height Ra defined in JIS B0601:2013. Here, the "interface between the coating and the base steel plate" refers to the actual interface between the coating and the base steel plate. If the roughness becomes larger, cracks are likely to occur due to stress concentration. The roughness of the interface between the coating and the base steel plate can be 2.5 μm or less or 2.0 μm or less in terms of Ra. Regarding the roughness of the interface between the coating and the base steel plate, the surface roughness of the base steel plate measured after the coating is removed can be regarded as the roughness of the interface between the coating and the base steel plate. The removal of the coating is performed by dissolving the coating in an acid solution to which an inhibitor for inhibiting corrosion of the steel plate is added.

[0102] [Ferrite phase outside the crimped portion]

[0103] In the welded joint of the present invention, at a position 500 μm in any direction outward from the end of the crimped portion, in the depth direction of the base steel plate starting from the interface between the plating layer of the plated steel plate and the base steel plate, the thickness of the layer having an area ratio of ferrite phase of 90% or more is 15 μm or more. Figure 2 An example of a SEM microstructure photograph of the welded portion and its vicinity of the welded joint of the present invention is shown. Figure 2 The black part on the upper right is the separation part. A layer with a ferrite (α) phase area ratio of more than 90% is formed on the surface of the steel plate on the lower side. The inside of the steel plate is martensite (M), and sometimes there is also a part of ferrite (α). In addition, a heat-affected zone (HAZ) is formed near the crimping part, where the structure changes due to welding heat.

[0104] It is known that the LME sensitivity of the grain boundary of the ferrite phase is lower than that of the γ (austenite) grain boundary (for example, Non-Patent Document 1). Therefore, by making the welded portion of the welded joint and the vicinity thereof a structure in which the ferrite phase is stable during welding, the LME suppression effect during the manufacture of the welded joint can be improved. As described above, such a surface structure can be obtained by setting the chemical composition of the base steel plate to a component containing a large amount of Si and Al, performing the heat treatment described below, and then performing spot welding.

[0105] If the thickness of the layer having an area ratio of 90% or more of the ferrite phase is 15 μm or more, the effect of improving the LME resistance can be obtained, so the upper limit of the thickness is not particularly limited, and the thickness may be, for example, 100 μm or less, 80 μm or less, or 60 μm or less. The thickness of the layer having an area ratio of 90% or more of the ferrite phase may be 20 μm or more or 30 μm or more.

[0106] The thickness of the layer with an area ratio of ferrite phase of 90% or more is determined by nitric acid etching of the cross section of the welded joint cut perpendicular to the steel plate surface and SEM observation, thereby distinguishing and determining martensite, bainite, ferrite, etc. based on their organizational morphology. Here, the area ratio of the ferrite phase refers to the area ratio determined by observing in the cross section cut perpendicular to the steel plate surface. Even if there is a portion with an area ratio of ferrite phase less than 90% when the cross section cut parallel to the steel plate surface is locally observed in the middle of the thickness direction, there is no problem if the area ratio of ferrite phase in the cross section cut perpendicularly to a depth of 15μm is 90% or more. A more specific measurement method is described as follows.

[0107] The ferrite area ratio was obtained by cutting a cross section in the thickness direction perpendicular to the rolling direction of the steel plate, mirror polishing, using nitric acid to present the steel structure, and taking a secondary electron image using an electric field emission scanning electron microscope. The observation position was 500 μm from the end of the crimped portion to the outside, in the rolling direction ( Figure 1 (b) The observation positions of 5 fields of view are determined at equal intervals at any position in the direction perpendicular to the paper surface) and observed. The ferrite area ratio is set to the average value of the 5 fields of view. For the obtained tissue photograph, the fraction of each tissue is calculated by the point counting method. More specifically, first, equally spaced grids are drawn on the tissue photograph. Next, it is determined whether the tissue of each lattice point corresponds to tempered martensite, pearlite, ferrite, primary martensite or retained austenite, or bainite. The number of lattice points corresponding to each tissue is calculated and divided by the total number of lattice points, thereby determining the fraction of each tissue. The more the total number of lattice points, the more accurately the volume fraction can be calculated. In this embodiment, the lattice spacing is set to 2μm×2μm, and the total number of lattice points is set to 1500 points.

[0108] The judgment criteria of tempered martensite, pearlite, ferrite, primary martensite or retained austenite, or bainite are shown. The region where the lower structure (lath boundary, block boundary) is present in the grain and carbides are precipitated with multiple variants is judged as tempered martensite. In addition, the region where cementite is precipitated in layers is judged as pearlite. The region where the brightness is small and the lower structure is not confirmed is judged as ferrite. The region where the brightness is high and the lower structure is not revealed by etching is judged as primary martensite or retained austenite. The region that does not meet any of the above is judged as bainite. Simply put, if it is distinguished from ferrite and other structures, the area ratio of the ferrite phase can be calculated.

[0109] [Tensile strength of plated steel sheet]

[0110] The present invention suppresses the generation of LME in high-strength steel plates, so the plated steel plates constituting the welded joints are high-strength, specifically having a tensile strength of 780 MPa or more. The upper limit of the tensile strength is not particularly limited, and from the viewpoint of ensuring toughness, the tensile strength may be, for example, 2000 MPa or less. The tensile strength is measured using a JIS No. 5 tensile test piece having a direction perpendicular to the rolling direction as the length direction, in accordance with JIS Z 2241:2011. The tensile strength may be 880 MPa or more, 980 MPa or more, 1080 MPa or more, or 1180 MPa or more. The tensile strength may be 1900 MPa or less, or 1800 MPa or less.

[0111] It should be noted that when it is impossible to take a test piece for measuring the tensile strength from the plated steel plate constituting the welded joint, as an alternative, the hardness (Vickers hardness) of the plated steel plate in the non-heat-affected zone located at a distance of more than 5 mm from the outer end of the spot weld is measured, and the value of the tensile strength can be estimated based on the following correlation formula (Correlation between static strength parameters, Norihiko Hasegawa, Junichi Arai, Michishichi Tanaka, "Materials" Vol. 39, No. 442, P859-863).

[0112] Hv=0.301×TS+5.701

[0113] (Wherein, Hv is Vickers hardness, TS is tensile strength (unit: MPa))

[0114] That is, when the hardness is about 240 Hv or more, it can be considered that the tensile strength is 780 MPa or more.

[0115] The hardness of the plated steel sheet is measured at the position of the non-heat-affected portion of the plated steel sheet constituting the welded joint, at a position of 1 / 2 depth. The hardness measurement is performed in accordance with JIS Z 2244:2009. The measurement load is set to 200 gf. The hardness of the plated steel sheet in the non-heat-affected portion at a distance of 5 mm or more from the outer end of the spot weld can be 245 Hv or more, 250 Hv or more, 260 Hv or more, 270 Hv or more, 300 Hv or more, or 340 Hv or more.

[0116] Next, a method for manufacturing a welded joint of the present invention will be described. First, a method for manufacturing a base steel plate of a plated steel plate constituting a welded joint will be described.

[0117] <Method for Manufacturing Base Steel Plate>

[0118] The base steel plate of the plated steel plate constituting the welded joint of the present invention can be obtained, for example, by the following manufacturing method: a casting step of casting molten steel with adjusted chemical composition to form a steel sheet; a hot rolling step of hot rolling the steel sheet to obtain a hot-rolled steel sheet; a coiling step of coiling the hot-rolled steel sheet; a cold rolling step of cold rolling the coiled hot-rolled steel sheet to obtain a cold-rolled steel sheet; a pre-treatment step of brush grinding the cold-rolled steel sheet; and an annealing step of annealing the cold-rolled steel sheet after the pre-treatment. Alternatively, the cold rolling may be directly performed without coiling after the hot rolling step, pickling, and cold rolling.

[0119] [Casting process]

[0120] The conditions of the casting process are not particularly limited, and for example, after smelting in a blast furnace, electric furnace, etc., various secondary smeltings are performed, and then casting is performed by a conventional continuous casting, casting using an ingot casting method, or thin slab casting.

[0121] [Hot rolling process]

[0122] Hot-rolled steel sheets are obtained by hot rolling the steel sheets obtained by casting. The hot rolling process is carried out in the following manner, that is, the cast steel sheets are directly or temporarily cooled and then heated and hot rolled. In the case of reheating, the heating temperature of the steel sheet can be, for example, 1100 to 1250°C. Rough rolling and finish rolling are usually carried out in the hot rolling process. The temperature and reduction rate of each rolling can be appropriately changed according to the desired metal structure and plate thickness. For example, the end temperature of the finish rolling can be 900 to 1050°C, and the reduction rate of the finish rolling can be 10 to 50%.

[0123] [Coiling process]

[0124] The hot-rolled steel sheet can be coiled at a predetermined temperature. The coiling temperature can be appropriately changed according to the desired metal structure, for example, 500 to 800°C. The hot-rolled steel sheet can also be uncoiled before or after coiling to give a predetermined heat treatment to the hot-rolled steel sheet. Alternatively, the hot-rolling process can be pickled without coiling and cold-rolled as described below.

[0125] [Cold rolling process]

[0126] After pickling the hot-rolled steel sheet, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The cold-rolling reduction ratio can be appropriately changed according to the desired metal structure and plate thickness, for example, 20 to 80%. After the cold-rolling process, the steel sheet can be cooled to room temperature, for example, by air cooling.

[0127] [Pre-treatment process]

[0128] As described above, in the welded joint, in the non-heat-affected zone, in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate, the depth at which the C concentration measured by GDS is 0.05% or less is 10 μm or more, and at a position 500 μm outward from the end of the crimped portion, in order to make the thickness of the layer having an area ratio of ferrite phase of 90% or more in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate be 15 μm or more, it is necessary to perform a prescribed pretreatment before annealing of the steel plate and then perform annealing.

[0129] The pretreatment includes grinding the surface of the cold-rolled steel sheet with a grinding brush (brush grinding treatment). As an example of a usable grinding brush, M-33 manufactured by HOTANI Corporation can be cited. In this way, strain can be introduced without increasing the roughness of the surface. During grinding, a 1.0-5.0% aqueous solution of NaOH can be applied to the surface of the steel sheet. The brush pressure reduction can be 0.5-10.0 mm, and the rotation speed can be 100-1000 rpm. By controlling the brush grinding treatment to such coating liquid conditions, brush pressure reduction, and rotation speed, decarburization is promoted in the annealing step described later, and a structure in which ferrite is also stable around the weld during the manufacture of the welded joint can be effectively formed on the surface of the steel sheet.

[0130] [Annealing process]

[0131] After the pretreatment process, the cold-rolled steel sheet is annealed. Annealing is performed under a tension of 1 to 20 MPa. If tension is applied during annealing, strain can be more effectively introduced into the steel sheet, promoting decarburization of the surface layer.

[0132] The holding temperature of the annealing process is set to 750-900°C. The holding temperature may be 770-870°C. By setting it in such a range, decarburization can be promoted, the C concentration of the surface layer can be reduced, and the ferrite phase can be stabilized. The heating rate to the holding temperature is not particularly limited, and it can be 1-10°C / second.

[0133] The holding time at the holding temperature in the annealing step is set to 20 to 300 seconds. The holding time may be 30 to 250 seconds. By setting the holding time in such a range, decarburization can be promoted, the C concentration in the surface layer can be reduced, and the ferrite phase can be stabilized.

[0134] The atmosphere of the annealing process is set to a dew point of -30 to 20°C. The dew point can be -10 to 5°C. The atmosphere can be, for example, N2-1 to 10 vol% H2, or N2-2 to 4 vol% H2. When the dew point is too high or too low, a phase containing oxides such as Si, Mn, and Al may be formed outside the steel sheet, interdiffusion between the plating component and the steel component may be hindered, and the plating property may become insufficient.

[0135] According to the production method including the above steps, decarburization is promoted in the surface layer of the steel plate, and a steel plate having a stable ferrite phase can be obtained even when a weld joint is produced.

[0136] <Method for producing plated steel sheet>

[0137] The plated steel sheet constituting the weld joint of the present invention can be obtained by performing a plating treatment to form a plated layer containing Zn on the base steel sheet produced as described above.

[0138] The plating treatment can be carried out according to methods known to those skilled in the art. The plating treatment can be carried out, for example, by melt plating or by electroplating. Preferably, the plating treatment is carried out by melt plating. The conditions of the plating treatment can be appropriately set in consideration of the chemical composition, thickness and adhesion amount of the desired coating. For example, it can be immersed in a molten zinc plating bath at 420 to 480° C. with adjusted chemical composition for 1 to 10 seconds, and after dipping, it can be pulled out at 20 to 200 mm / s, and the coating adhesion amount can be controlled by N2 wiping gas. After the plating treatment, an alloying treatment can be carried out. The alloying treatment can be carried out, for example, at 500 to 550° C. for 10 to 60 seconds.

[0139] <Spot welding process>

[0140] A plurality of steel plates including the above-mentioned plated steel plates are overlapped and spot welded to obtain a welded joint. The conditions for spot welding are not particularly limited. For example, a dome-shaped welding electrode with a tip diameter of 6 to 8 mm can be used to perform spot welding with a pressure of 1.5 to 6.0 kN, a current of 0.1 to 1.0 seconds, and a current of 4 to 15 kA.

[0141] The welded joint of the present invention can suppress LME cracks during production and can therefore be suitably used in a wide range of fields such as automobiles, home appliances, and building materials, and is particularly preferably used in the automobile field.

[0142] Example

[0143] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.

[0144] <Example 1>

[0145] (Preparation of Plated Steel Sheet Samples)

[0146] Molten steel adjusted to the chemical composition described in No. 1 of Table 1 was melted in a blast furnace and cast by continuous casting to obtain a steel sheet. The obtained steel sheet was heated to 1200°C, the finishing temperature of the finish rolling was set to 950°C, the reduction rate of the finish rolling was 30%, and hot rolling was performed to obtain a hot-rolled steel sheet. The obtained hot-rolled steel sheet was coiled at a coiling temperature of 650°C, pickled, and then cold rolled at a reduction rate of 50% to obtain a cold-rolled steel sheet. The thickness of the cold-rolled steel sheet was 1.6 mm.

[0147] Next, the cold-rolled steel sheet was coated with a 2.0% aqueous solution of NaOH and subjected to brush grinding pretreatment. In the brush grinding, M-33 manufactured by Hotani Co., Ltd. was used as a grinding brush, with a brush reduction of 2.0 mm and a rotation speed of 600 rpm (Condition A in Table 2).

[0148] Before the annealing step, the surface roughness of the steel sheet was measured according to JIS B 0601: 2013. Specifically, 10 locations were randomly selected on the surface of the surface layer side, and the surface profile was measured at each location using a contact type surface roughness meter. The surface roughness of these locations was arithmetically averaged to obtain an arithmetic average roughness Ra, which was evaluated as follows.

[0149] Evaluation AA: 2.0μm or less

[0150] Evaluation A: more than 2.0 μm and less than 3.0 μm

[0151] Evaluation B: more than 3.0 μm

[0152] Then, annealing treatment was performed in a furnace with an oxygen concentration of less than 20 ppm in a N2-4% H2 gas atmosphere under the conditions of a dew point of 0°C, a holding temperature of 800°C, and a holding time of 100 seconds. The heating rate during annealing was 6.0°C / second to 500°C and 2.0°C / second from 500°C to the holding temperature. Annealing treatment was performed under a tension of 15 MPa.

[0153] After annealing, the steel sheet was plated to obtain a hot-dip zinc plated steel sheet. The plated steel sheet was immersed in a hot-dip zinc bath (Zn-0.2% Al) at 460°C for 3 seconds. After immersion, the steel sheet was pulled out at 100 mm / sec and the coating weight was controlled to 50 g / m by using N2 wiping gas. 2 , and obtain a plated steel sheet.

[0154] <Examples 2 to 28, Comparative Examples 29 to 41>

[0155] The plated steel sheet was manufactured in the same manner as in Example 1 except that the chemical composition was set to the composition described in Table 1, the conditions of the pretreatment process and the annealing process were set to the conditions described in Table 2, and the type of plating was set to the type described in Table 3. In addition, in No. 40, the pretreatment of brush grinding was omitted. In No. 41, D-100 manufactured by HOTANI Co., Ltd. was used as a grinding brush in the pretreatment (Condition B in Table 2). D-100 is a brush with a grinding amount that is about twice that of M-33.

[0156] The composition and bath temperature of the plating types shown in Table 3 are as follows: F After the plating treatment, alloying treatment was performed at 530° C. for 20 seconds to obtain alloyed hot-dip zinc plating.

[0157] A: Zn-0.2%Al (460℃)

[0158] B: Zn-0.5%Al (440℃)

[0159] C: Zn-1.5%Al-1.5%Mg (500℃)

[0160] D: Zn-20%Al-7%Mg (530℃)

[0161] E: Zn-30%Al-10%Mg (530℃)

[0162] F: Zn-0.14%Al (450℃) alloyed hot-dip zinc plating

[0163] Table 1

[0164]

[0165] ※Underlined elements are outside the scope of the present invention.

[0166] Table 2

[0167]

[0168] ※The underlined characters are outside the range of the preferred production method.

[0169] (Tensile Strength Evaluation)

[0170] For each plated steel sheet, a JIS No. 5 tensile test piece having a longitudinal direction perpendicular to the rolling direction was taken and subjected to a tensile test in accordance with JIS Z 2241:2011 to obtain the tensile strength and evaluate it as follows.

[0171] Rating AAA: 1180MPa or above

[0172] Evaluation AA: 980MPa or more and less than 1180MPa

[0173] Evaluation A: 780MPa or more and less than 980MPa

[0174] (Production of welded joints)

[0175] Two of each plated steel sheet were overlapped and spot welding was performed using a dome-radius type welding electrode with a tip diameter of 8 mm at an angle of 2°, a pressure of 4.0 kN, a current of 0.5 seconds, and a current of 12 kA to produce a welded joint, and the LME suppression effect (LME resistance) during production was evaluated.

[0176] The LME resistance was evaluated as follows based on the length of LME cracks generated near the outer side of the crimped portion of the weld. Figure 3 , the evaluation of LME resistance is described. LME resistance is evaluated by measuring the length of LME cracks generated in the part outside the crimping part 3 formed by overlapping two steel plates 1 and spot welding, that is, near the crimping part, that is, near the outside of the crimping part. According to the length of the crack 11 near the outside of the crimping part, the evaluation is as follows. In this embodiment, if the evaluation is A or above, it is judged that the LME resistance is excellent. If the evaluation is "A" or above, the LME resistance is excellent, and it is judged that the technical problem to be solved by the present invention has been solved.

[0177] Rating AAA: 0μm

[0178] Evaluation AA: more than 0μm and less than 60μm

[0179] Evaluation A: 60 μm or more and less than 120 μm

[0180] Evaluation B: 120μm or more

[0181] (Evaluation of the structure around the weld)

[0182] The welded joint was cut and a sample was collected. At the position of the non-heat-affected zone, with the interface between the coating and the base steel plate as the starting point, GDS measurements were performed 5 times along the plate thickness direction under the aforementioned conditions to determine the depth at which the C concentration was 0.05% or more, which is shown in "C ≤ 0.05% depth" in Table 3.

[0183] In addition, at the position that became the non-heat-affected zone, the plating was removed using a 10 mass % hydrochloric acid solution to which 0.06 mass % inhibitor (manufactured by Asahi Chemical Industries, Ltd., IBIT) was added, and the roughness of the surface of the exposed base steel plate was measured by the same method as before annealing, and the results are shown in the "base steel plate / plating interface roughness" in Table 3.

[0184] In addition, at a position 500 μm outward from the end of the crimped portion, with the interface between the coating layer and the base steel plate as the starting point, the thickness of the layer having an area ratio of ferrite phase of 90% or more was measured by the above method and shown in “α phase thickness” in Table 3.

[0185] Table 3 shows the evaluation results.

[0186] Table 3

[0187]

[0188] ※ Underlined elements are outside the scope of the present invention or the expected properties cannot be obtained.

[0189] No. 29 is a comparative example in which the C content of the base steel plate of the plated steel plate is high. It is believed that the C content of the base steel plate is high, so even through high dew point annealing, decarburization in the surface layer does not proceed. Therefore, the depth of the non-heat-affected portion where the C concentration is 0.05% or less becomes smaller, and the thickness of the layer where the area ratio of the ferrite phase is 90% or more at a position 500 μm outside from the end of the crimping portion becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0190] No. 30 is a comparative example in which the Si content of the base steel plate of the plated steel plate is small and the sum of the Si and sol. Al contents is small. It is believed that the Si content of the base steel plate is small, so even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and the ferrite is not stabilized. Therefore, the depth of the non-heat-affected portion where the C concentration is less than 0.05% becomes smaller, and the thickness of the layer where the area ratio of the ferrite phase is more than 90% from the end of the crimping portion to the outside 500μm becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0191] No. 31 is a comparative example in which the Si content of the base steel plate of the plated steel plate is high. It is believed that since the Si content of the base steel plate is high, even if high dew point annealing is performed, external oxidation advances, and oxides (scale) are formed on the surface layer of the steel plate, suppressing decarburization on the outermost surface. Therefore, the depth at which the C concentration in the non-heat-affected zone is 0.05% or less becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0192] No. 32 is a comparative example in which the sol. Al content of the base steel plate of the plated steel plate is small. It is believed that the sol. Al content of the base steel plate is small, so even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and the ferrite is not stabilized. Therefore, the depth of the non-heat-affected portion where the C concentration is less than 0.05% becomes smaller, and the thickness of the layer where the area ratio of the ferrite phase is more than 90% from the end of the crimping portion to the outside 500μm becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0193] No. 33 is a comparative example in which the sol. Al content of the base steel plate of the plated steel plate is small and the sum of the contents of Si and sol. Al is small. It is believed that the sol. Al content of the base steel plate is small and the sum of the contents of Si and sol. Al is small, so even if high dew point annealing is performed, decarburization of the surface layer does not proceed and ferrite is not stabilized. Therefore, the depth of the non-heat-affected zone where the C concentration is less than 0.05% becomes smaller, and the thickness of the layer where the area ratio of the ferrite phase is more than 90% from the end of the crimping portion to the outside 500μm becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0194] No. 34 is a comparative example in which the sol. Al content of the base steel plate of the plated steel plate is high. It is believed that the sol. Al content of the base steel plate is high, so even if high dew point annealing is performed, external oxidation advances, and oxides (scale) are formed on the surface layer of the steel plate, which inhibits decarburization on the outermost surface. Therefore, the depth at which the C concentration in the non-heat-affected zone is 0.05% or less becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0195] No. 35 is a comparative example in which the total content of Si and Al in the base steel plate of the plated steel plate is small. It is believed that the sum of the content of Si and sol.Al in the base steel plate is small, so even if high dew point annealing is performed, decarburization of the surface layer does not proceed, and the ferrite is not stabilized. Therefore, the depth of the non-heat-affected portion where the C concentration is less than 0.05% becomes smaller, and the thickness of the layer where the area ratio of the ferrite phase is more than 90% from the end of the crimping portion to the outside 500μm becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0196] No. 36 Since the dew point during annealing during the production of the plated steel sheet was low, it is believed that a layer containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, and the mutual diffusion of the plating components and the steel components was hindered during the plating process. As a result, appropriate plating was not obtained, and therefore the weld joint was not evaluated.

[0197] No. 37 Since the dew point during annealing during the production of the plated steel sheet was high, it is believed that a layer containing oxides such as Si, Mn, and Al was formed on the outside of the steel sheet during annealing, and the mutual diffusion of the plating components and the steel components was hindered during the plating process. As a result, appropriate plating was not obtained, and therefore the weld joint was not evaluated.

[0198] In No. 38, the holding temperature during annealing during the manufacture of the plated steel sheet was low, so it is believed that decarburization was not sufficiently promoted during annealing. Therefore, the depth of the non-heat-affected portion where the C concentration was 0.05% or less became smaller, and the thickness of the layer where the area ratio of the ferrite phase was 90% or more at a position 500 μm outside from the end of the crimped portion became smaller. As a result, the LME resistance during the manufacture of the welded joint was poor.

[0199] No. 39 is a comparative example in which the annealing temperature during the manufacture of the plated steel sheet is high. It is believed that the holding temperature during annealing is high, so decarburization is not sufficiently promoted during annealing. Therefore, the depth of the non-heat-affected portion where the C concentration is 0.05% or less is reduced, and the thickness of the layer where the area ratio of the ferrite phase is 90% or more at a position 500 μm from the end of the crimping portion to the outside is reduced. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0200] No. 40 is a comparative example in which the annealing time during the manufacture of the plated steel sheet is short. It is believed that the holding time during annealing is short, so decarburization is not sufficiently promoted during annealing. Therefore, the depth of the non-heat-affected portion where the C concentration is 0.05% or less becomes smaller, and the thickness of the layer where the area ratio of the ferrite phase is 90% or more at a position 500 μm outside from the end of the crimping portion becomes smaller. As a result, the LME resistance during the manufacture of the welded joint is poor.

[0201] No. 41 was not subjected to brush grinding in the pre-treatment process when the plated steel sheet was manufactured, so it is believed that no strain was introduced into the surface of the steel sheet, and decarburization did not proceed during annealing. Therefore, the depth of the non-heat-affected portion where the C concentration was 0.05% or less became smaller, and the thickness of the layer where the area ratio of the ferrite phase was 90% or more at a position 500 μm outside from the end of the crimped portion became smaller. As a result, the LME resistance during the manufacture of the welded joint was poor.

[0202] In the pre-treatment process of No. 42 when manufacturing the plated steel sheet, a brush with a large amount of grinding was used, so the roughness of the surface of the base steel sheet became large, and the ferrite phase was unstable. Therefore, the thickness of the layer with an area ratio of ferrite phase of 90% or more at a position 500 μm outside from the end of the crimping part became smaller. As a result, the LME resistance during the manufacture of the welded joint was poor.

[0203] No. 1 to 28 are examples of the present invention, and LME during the manufacture of welded joints was suppressed. In examples where the depth of the non-heat-affected zone with a C concentration of 0.05% or less and the thickness of the layer with an area ratio of ferrite phase of 90% or more at a position 500 μm outside the end of the crimped portion were large, particularly excellent LME resistance was confirmed.

[0204] Industrial Applicability

[0205] According to the present invention, a weld joint in which LME cracks are suppressed during manufacturing can be provided, and the weld joint can be suitably used in applications such as automobiles, home appliances, and building materials, and is particularly suitably used in automobiles. Therefore, the present invention is an invention with extremely high industrial applicability.

[0206] Description of Reference Numerals

[0207] 1 Steel Plate

[0208] 2Nugget

[0209] 3Crimp part

[0210] 4 Separation

[0211] 5Heat affected area

[0212] 6 Overlapping surfaces

[0213] 11 Cracks near the outside of the crimping part

Claims

1. A welding joint, characterized in that: The invention comprises a plurality of overlapping steel plates, a nugget for joining the plurality of steel plates, a spot welding portion having a crimping portion and a heat-affected portion formed around the nugget, and a separation portion formed around the crimping portion. At least one of the plurality of steel plates is a plated steel plate having a base steel plate and a plated layer, wherein the plated layer is formed at least on a surface corresponding to an overlapping surface of the plurality of steel plates and contains Zn. The tensile strength of the plated steel sheet is 780 MPa or more. The chemical composition of the base steel plate includes, by mass%, the following: C:0.05~0.40%、 Si: 0.7-3.0%, Mn: 0.1-5.0%, Sol.Al: 0.7~2.0%, P: 0.0300% or less, S: 0.0300% or less, N: 0.0100% or less, B:0~0.010%、 Ti: 0~0.150%, Nb: 0~0.150%, V:0~0.150%、 Cr:0~2.00%、 Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W:0~1.00%、 Ca: 0~0.100%, Mg: 0~0.100%, Zr:0~0.100%、 Hf: 0~0.100%、 REM: 0~0.100% The balance is Fe and impurities. The total content of Si and sol.Al is 1.8% or more. In the non-heat-affected zone of the weld joint, In the depth direction of the base steel sheet starting from the interface between the plated layer of the plated steel sheet and the base steel sheet, the depth at which the C concentration measured by GDS is 0.05% or less is 10 μm or more, The roughness of the interface between the plated layer of the plated steel sheet and the base steel sheet is 3.0 μm or less in terms of Ra. At a position 500 μm outward from the end of the crimping portion, The thickness of the layer having an area ratio of ferrite phase of 90% or more in the depth direction of the base steel sheet starting from the interface between the plated layer of the plated steel sheet and the base steel sheet is 15 μm or more.

2. The welded joint according to claim 1, characterized in that: In the non-heat-affected zone of the weld joint, the depth where the C concentration measured by GDS is 0.05% or less is 15 μm or more in the depth direction of the base steel plate starting from the interface between the plating layer of the plated steel plate and the base steel plate.

3. The welded joint according to claim 1, characterized in that: At a position 500 μm outward from the end of the crimped portion, in the depth direction of the base steel plate starting from the interface between the plating layer of the plated steel plate and the base steel plate, the thickness of the layer having an area ratio of ferrite phase of 90% or more is 30 μm or more.

4. The welded joint according to claim 1, characterized in that: In the non-heat-affected zone of the weld joint, in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate, the depth at which the C concentration measured by GDS is less than 0.05% is 15 μm or more, and at a position 500 μm outward from the end of the crimped portion, in the depth direction of the base steel plate starting from the interface between the coating layer of the plated steel plate and the base steel plate, the thickness of the layer having an area ratio of ferrite phase of 90% or more is 30 μm or more.

5. The welded joint according to any one of claims 1 to 4, characterized in that: The roughness of the interface between the plating layer of the plated steel sheet and the base steel sheet in the non-heat-affected portion is 2.0 μm or less in terms of Ra.

Citation Information

Patent Citations

  • Steel sheet, hot-dip zinc-coated steel sheet, and alloyed hot-dip zinc-coated steel sheet

    WO2019116531A1

  • Steel sheet

    WO2020218575A1